Artificial Intelligence (AI)-based Learning Media: Definition, Bibliometric, Classification, and Issues for Enhancing Creative Thinking in Education - Solihat, Ai Nur; Dahlan, Dadang; Kusnendi, K.; Susetyo, Budi; Al Obaidi, Abdulkareem Sh. Mahdi (Universitas Pendidikan Indonesia (UPI), 2024)
This research aims to identify effective ways of integrating Artificial Intelligence (AI) technology with innovative learning methods to improve students' creative thinking skills in various educational contexts. The bibliometric method, a quantitative and statistical approach to bibliographic data such as publications and citations, serves as the research method. Data were collected on July 2024, through the SCOPUS database using the keywords